Development, Assessment, and Outcomes of a Community-Based Model of Antiretroviral Care in Western Kenya Through a Cluster-Randomized Control Trial. (1st June 2021) - Goodrich, Suzanne; Siika, Abraham; Mwangi, Ann; Nyambura, Monicah; Naanyu, Violet; Yiannoutsos, Constantin; Spira, Thomas; Bateganya, Moses; Toroitich-Ruto, Cathy; Otieno-Nyunya, Boaz; Wools-Kaloustian, Kara
Abstract : Objective: To develop and assess an alternative care model using community-based groups for people living with HIV and facilitate by lay personnel. Methods: Geographic locations in the Academic Model Providing Access to Healthcare Kitale clinic catchment were randomized to standard of care versus a community-based care group (ART Co-op). Adults stable on antiretroviral therapy and virally suppressed were eligible. Research Assistant–led ART Co-ops met in the community every 3 months. Participants were seen in the HIV clinic only if referred. CD4 count and viral load were measured in clinic at enrollment and after 12 months. Retention, viral suppression, and clinic utilization were compared between groups using χ 2, Fisher exact, and Wilcoxon rank sum tests. Results: At 12 months, there were no significant differences in mean CD4 count or viral load suppression. There was a significant difference in patient retention in assigned study group between the intervention and control group (81.6% vs 98.6%; P < 0.001), with a number of intervention patients withdrawing because of stigma, relocation, pregnancy, and work conflicts. All participants, however, were retained in an HIV care program for the study duration. The median number of clinic visits was lower for the intervention group than that for the control group (0 vs 3; P < 0.001). Conclusions: Individuals retained in a community-based HIV care model had clinical outcomes equivalent to those receiving clinic-based care. This innovative model of HIV care addresses the problems of insufficient health care personnel and patient retention barriers, including time, distance, and cost to attend clinic, and has the potential for wider implementation.